Functionalized screen-printed electrodes for the thermal detection of Escherichia coli in dairy products. (15th March 2023) - Arreguin-Campos, Rocio; Frigoli, Margaux; Caldara, Manlio; Crapnell, Robert D.; Ferrari, Alejandro Garcia-Miranda; Banks, Craig E.; Cleij, Thomas J.; Diliën, Hanne; Eersels, Kasper; van Grinsven, Bart
Highlights: Screen-printed electrodes (SPEs) are functionalized via a facile polymer-imprinting protocol for the preparation of synthetic receptors for Escherichia coli . The functionalized SPEs were employed for the thermal detection of E. coli for the first time. The device is able to detect the model microorganism with a limit of detection of 180 CFU/mL. The platform is validated in milk, demonstrating its suitability and reproducibility in comparison to experiments in buffer. Abstract: Accurate and fast on-site detection of harmful microorganisms in food products is a key preventive step to avoid food-borne illness and product recall. In this study, screen-printed electrodes (SPEs) were functionalized via a facile strategy with surface imprinted polymers (SIPs). The SIP-coated SPEs were used in combination with the heat transfer method (HTM) for the real-time detection of Escherichia coli . The sensor was tested in buffer, with a reproducible and sensitive response that attained a limit of detection of 180 CFU/mL. Furthermore, selectivity was assessed by analyzing the sensor's response to C. sakazakii, K. pneumoniae and S. aureus as analogue strains. Finally, the device was successfully used for the detection of E. coli in spiked milk as proof-of-application, requiring no additional sample preparation. These results suggest the proposed thermal biosensor possesses the potential of becoming a tool for routine, on-site monitoring of E. coli in food safety applications.